2006
DOI: 10.1017/s0033291706007835
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of positive mood induction in euthymic bipolar subjects compared with healthy controls

Abstract: Background. Demonstrating differences between euthymic bipolar subjects and healthy controls in response to positive (happy) mood induction may help elucidate how mania evolves. This pilot study evaluates the Go task in a reward paradigm as a method for inducing a happy mood state and compares the response of euthymic bipolar subjects and healthy controls.Method. The Sense of Hyperpositive Self Scale, the Tellegen positive and negative adjectives, the Global-Local task and a visual analogue scale for measuring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 20 publications
4
54
0
Order By: Relevance
“…For the PANAS only we used a 3 9 3 9 2 design, as it was completed three times, with the third assessment at the end to explore whether mood effects last longer in patients with BD (see Farmer et al 2006). The two between-subject factors were 'group' (UD, BD, or HC), and 'experimental condition' (upward and downward social comparison).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the PANAS only we used a 3 9 3 9 2 design, as it was completed three times, with the third assessment at the end to explore whether mood effects last longer in patients with BD (see Farmer et al 2006). The two between-subject factors were 'group' (UD, BD, or HC), and 'experimental condition' (upward and downward social comparison).…”
Section: Methodsmentioning
confidence: 99%
“…The studies reported above provide indirect evidence to predict that favourable downward comparisons will have a positive effect on mood and self-esteem especially in people with BD. Based on Farmer et al (2006) results demonstrating a prolonged elevated happiness after a positive mood induction in patients with BD, it could even be assumed that such positive effects on mood from downward social comparisons might last longer in patients with BD than healthy controls.…”
Section: Bipolar Disorder and Social Comparisonsmentioning
confidence: 99%
“…It has been suggested that these symptoms may reflect upregulation of the mesolimbic DA system in bipolar disorder [266]. Behavioral studies of response to rewards in bipolar disorder indicate deficits in behavioral adaptation to changing reward contingencies [267] and prolonged elevation of mood in response to monetary reward in euthymic patients with bipolar disorder [268]. Reward motivation is also atypical in individuals with bipolar disorder, as shown by a self-report measure of reward responsivity [269] and in eye-tracking studies of monetary gains and losses [270].…”
Section: Reviewmentioning
confidence: 99%
“…Deficits in performing response-reversal tasks, modeling behavioral adaptation to changing reward contingencies in euthymic children with bipolar disorder, support this notion (Gorrindo et al, 2005). Further, it has been shown that induction of happy mood with a reward task results in prolonged elevated mood in euthymic bipolar patients compared to healthy controls (Farmer et al, 2006).…”
Section: Introductionmentioning
confidence: 97%
“…We designed this study to test two hypotheses: (1) Medicated bipolar patients during an acute manic episode will show deficient reward processing (Miller, 1993;Johnson, 2005;Gorrindo et al, 2005;Farmer et al, 2006) in the form of decreased reward-related brain activation. (2) Medicated patients during an acute episode of schizophrenia or schizoaffective disorder will not show similarly decreased reward-related brain activation (Juckel et al, 2006b), which provides evidence that the anticipated changes in medicated, manic patients are not simply due to an acute psychiatric illness or due to treatment with neuroleptic medication.…”
Section: Introductionmentioning
confidence: 99%